The potential of Jamblang Bark Actived Carbon (Syzygium cumini) in Reducing Lead Heavy Metal (Pb) Levels - Himyatul Hidayah; Amalia; Lora Irawan; Yuliani, Nisa Dwi (HM Publisher, 2024)
Jamblang wood, also known as jambolin or jambolan, is a plant that is widespread in various tropical regions, including Indonesia. Jamblang bark has great potential as a source of raw material for making active carbon because it is rich in organic compounds, cellulose, and lignin, which can provide an ideal pore structure to capture and bind heavy metals. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of jamblang bark (Syzygium cumini) activated carbon in reducing lead heavy metal (Pb) levels. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Activated carbon produced from jamblang bark (Syzygium cumini) has significant potential in reducing levels of heavy metal lead (Pb) in various wastewater treatment settings, drinking water treatment, and recovery of heavy metals from industrial waste.